Professionally oriented approach to the study of the section "integral calculus" in the training of specialists of the economic profile - Nataliya V. Spiridonova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Mathematics is the foundation of technical education and in the practical work of any specialist is supposed to solve professional problems. Therefore, mathematical training in a technical university is to the form the mathematical competence of students in accordance with their qualification with the help of professionally-oriented examples. The article considers and establishes the practical use of the section of mathematical analysis "Integral calculus" in solving economic problems.